Letter (copy) : International Brigade Dependants' Fund - Citrine, Walter, 1887-1983
034-0121-001 Secretary's. WMC/HVT/EK/1217. 8th June, 1938. Mr. A. Taylor, The Rossendale Union of Boot, Shoe and Slipper Operatives, Tenterfield Street, Waterfoot, ROSSENDALE. Dear Mr. Taylor, International Brigade Dependants Fund. I have your letter of the 7th June in regard to the above matter. The question of a grant to this body from the International Solidarity Fund has been considered by the General Council, but in view of the fact that our appeal for Spain was made specifically for Spanish workers no grant was given nor did the General Council render any assistance from their general funds. When certain individuals were responsible for recruiting for Spain we saw the problems which were likely to arise in regard to subsequent responsibilities. The Committee is not a proscribed organisation, but all the funds we receive for Spain are being used for the relief of refugees of the civilian population. Yours sincerely, General Secretary. 292/946/34/121